Insight into insect trypanosomatid biology via whole genome sequencing - Skalický, Tomáš (Jihočeská univerzita, 2017)
This thesis is composed of two topics both concerning diverse and obligatory trypanosomatid parasites. First part deals with identification of new Trypanosoma species identified in blood meal of tsetse flies caught in Dzanga-Sangha Protected Areas, Central African Republic, and identification of feeding preferences of tsetse flies. The second part concerns extraordinary monoxenous trypanosomatid Paratrypanosoma confusum which constitutes the most basal branch between free-living Bodo saltans and parasitic trypanosomatids. This thesis helped to elucidate morphology and biology of this deep branching trypanosomatid. Using genome and transcriptome sequencing and comparative bioinformatics approaches enabled search for ancestral genes shared with free-living bodonids and confirmed genome streamlining in trypanosomatids.
Insight into insect trypanosomatid biology via whole genome sequencing
Keywords: Trypanosomatid; evolution; diversity; flagellar remodeling; haptomonads; cytostome; Trypanosomatid; evolution; diversity; genome sequencing; flagellar remodeling; haptomonads; cytostome